2022
DOI: 10.3390/nano12111849
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Mechanical Anisotropy of Protein Structures in the Unfoldase Mechanism of AAA+ Molecular Machines

Abstract: Essential cellular processes of microtubule disassembly and protein degradation, which span lengths from tens of μm to nm, are mediated by specialized molecular machines with similar hexameric structure and function. Our molecular simulations at atomistic and coarse-grained scales show that both the microtubule-severing protein spastin and the caseinolytic protease ClpY, accomplish spectacular unfolding of their diverse substrates, a microtubule lattice and dihydrofolate reductase (DHFR), by taking advantage o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…12,14,16,17 Several proposed mechanisms are: unfoldase, which is similar to the hand-over-hand action, wedge-like, or a combined unfoldase and wedge named death-spiral. 16,1820 Our previous studies showed that, while the unfoldase action is important, 21,22 the wedge mechanism is most likely making a large contribution to the disassembly of a microtubule by severing proteins. 2325…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,14,16,17 Several proposed mechanisms are: unfoldase, which is similar to the hand-over-hand action, wedge-like, or a combined unfoldase and wedge named death-spiral. 16,1820 Our previous studies showed that, while the unfoldase action is important, 21,22 the wedge mechanism is most likely making a large contribution to the disassembly of a microtubule by severing proteins. 2325…”
Section: Introductionmentioning
confidence: 99%
“…27 Interestingly, the disassembly of the hexameric state into lower order oligomers also occurred in our recent simulations of the action of spastin on microtubule filaments, especially when the interactions between the severing machine and the microtubule surface reach levels comparable to the interactions between kinesin-1 motors and microtubules. 22…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations